Sensitivity of High-latitude Freshwater Ecosystems to Global Change: Temperature and Solar Ultraviolet Radiation - Vincent, Warwick; Pienitz, Reinhard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Freshwater ecosystems are a major component of the northern environment. The application of new limnological technologies and approaches to these ecosystems is producing a revised perspective on their structure and dynamics, and is leading to insights into their potential response to global change processes.The planktonic communities of northern lakes are dominated by microbial food webs, with components that are highly sensitive to changes in temperature. North-south transects in Quebec, Yukon and the Northwest Territories show that lakes beyond the northern tree line have concentrations of UV-screening dissolved organic carbon less than 5 mg-l'1, rendering them vulnerable to changes in incident UVB and to climatic effects on catchment hydrology. The coupling of studies on the modern-day limnology of northern freshwater ecosystems with paleolimnological approaches will allow the interpretation of short-term changes in these systems within the context of their historical variability.